Osteochondral allograft transplantation in the football player (knee and ankle) - Tim Wang; William D. Bugbee (Elsevier, 2022)
Articular cartilage defects in the knee and ankle are frequently seen in football (soccer) players and are often a result of trauma, but occasionally are the consequence of occult underlying conditions such as osteochondritis dissecans. Symptoms such as pain, swelling, and inability to ramp up may limit an athlete's performance and ability to compete. Initial evaluation includes a careful history and physical exam, including assessment of overall limb and joint alignment, ligamentous stability, meniscal damage, as well as associated degenerative change. Though nonoperative management serves as the mainstay for treatment in high-level athletes, surgical options are indicated in situations where symptoms persist. Osteochondral allograft (OCA) transplantation, in particular, allows for restoration of hyaline cartilage with predictable healing and accelerated return to activity. With appropriate indications and surgical technique, graft survival following OCA transplantation can exceed 90% at 10 years postoperatively, allow for predictable (70%-80%) return to sport, and produce clinically meaningful improvements in patient-reported outcomes. Full return to sports is often possible between 4 and 10 months postoperatively. Careful attention to postoperative rehabilitation and strength progression prior to return to sport is imperative to prevent graft overload, joint inflammation, or secondary injury to other knee structures such as meniscus or ligamentous structures. This article reviews the overall indications, technique, and outcomes of OCA transplantation in the athletic population.